Kolaborasi Multi-Sektoral dalam Penguatan Branding, Packaging, dan Akses Pasar Madu Lokal untuk Mendukung Pembangunan Berkelanjutan - Mimin Sundari Nasution; Dadang Mashur; zulkarnaini zulkarnaini; Taryono Taryono; Harapan Tua; Masrul Ikhsan; Arya Arismaya Metananda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
This community service program aims to enhance the competitiveness of the local honey product “Madu Biene” in Bengkalis Regency through strengthening branding, packaging, and market access to support sustainable development. Prior to implementation, the partner MSME had no Trade Business License (IUD), which hindered market expansion and formal cooperation. The method employed was Participatory Action Research (PAR), involving local government, entrepreneurs, academics, communities, and the private sector as strategic partners. Activities included training on brand identity design, development of eco-friendly packaging, facilitation of online and offline marketing, and socialization as well as assistance in obtaining the IUD. The results showed improvements in packaging quality and brand image, expansion of marketing networks, increased understanding of sustainability principles among business actors, and the issuance of the IUD, which strengthened business legality. Multi-sectoral collaboration proved effective as a catalyst for empowering MSMEs based on local resources, while contributing to the achievement of SDGs, particularly goals 8, 12, and 17.